PENGARUH PENGEMBANGAN OBJEK WISATA PANTAI PASIR PANJANG TERHADAP PENDAPATAN PELAKU USAHA DI DESA NGILNGOF KABUPATEN MALUKU TENGGARA - Bwariat, Milus Andrityaman; Pelamonia, Merryll; Rehatta, Geradin (Jurnal Administrasi Terapan, 2022)
This study aims to determine the effect of developing long sand beach tourism objects on the income of business actors in Ngilngof Village, Southeast Maluku Regency. The sample in this study were 45 business actors on Pasir Panjang Beach. The data collection technique in this study was a questionnaire. The analytical technique used in this study was simple linear regression analysis, t-test analysis, validity test, normality test reliability test, heteroscedasticity test. The results of the study show that the long sand beach tourist attraction greatly affects the income of business actors because long sand beach is good for business land because many tourists always and want to visit long sand beach attractions.Keywords: Tourist Attractions, Income of Business Actors.